2017
DOI: 10.3389/fpsyg.2017.00068
|View full text |Cite
|
Sign up to set email alerts
|

All You Need Is Facebook Friends? Associations between Online and Face-to-Face Friendships and Health

Abstract: Positive social relations are known to have a beneficial impact on health, however, little is known about the links of health with online relationships. In this study, we compare face-to-face and virtual friendships in their association with health. By building on previous results of studies conducted on the well-being of college students, we expect to find stronger associations of face-to-face friendships with health than of those established through Facebook. Furthermore, we expect to test the mediating role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Consistent with our cohort-level findings, two studies found declines in face-to-face social interaction in samples of non-U.S. adults (Patulny & Seaman, 2017; Vilhelmson, Elldér, & Thulin, 2018) collected anew each year. In contrast, when individuals were followed longitudinally or assessed cross-sectionally, social media use promoted the development of strong ties in core discussion networks (Vriens & van Ingen, 2018) and was linked to more face-to-face interaction (Hall, Kearney, & Xing, 2018; Lima et al, 2017). This distinction between the individual and group level of analysis may help resolve the debate in the literature over displacement versus complementarity of in-person social interaction and social media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our cohort-level findings, two studies found declines in face-to-face social interaction in samples of non-U.S. adults (Patulny & Seaman, 2017; Vilhelmson, Elldér, & Thulin, 2018) collected anew each year. In contrast, when individuals were followed longitudinally or assessed cross-sectionally, social media use promoted the development of strong ties in core discussion networks (Vriens & van Ingen, 2018) and was linked to more face-to-face interaction (Hall, Kearney, & Xing, 2018; Lima et al, 2017). This distinction between the individual and group level of analysis may help resolve the debate in the literature over displacement versus complementarity of in-person social interaction and social media.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals high in extraversion, a trait valuing interaction with others and sociability, also have more friends on social media sites (Liu & Campbell, 2017; Whaite, Shensa, Sidani, Colditz, & Primack, 2018). This “rich get richer” hypothesis proposes that some people engage in both more digital and more face-to-face communication (Liang & Fu, 2015; Lima, Marques, Muinos, & Camilo, 2017). Thus, cohort-level displacement of in-person social interaction by digital media on average may coexist with individual-level complementarity between digital media use and in-person social interaction.…”
Section: Time Displacement At Cohort Versus Individual Levels Of Analysismentioning
confidence: 99%
“…Five studies (Jang et al, 2016;Lima et al, 2017;McCloskey et al, 2015;Wright, 2012;Zhang, 2017) were identified that focused on the effects of Facebook-based social support on aspects of general mental health. Overall, it was found that Facebook-based social support was predictive of better mental health, as well as decreased levels of mental distress (Jang et al, 2016;Lima et al, 2017;McCloskey et al, 2015;Wright, 2012;Zhang, 2017). Facebook-based social support was found to predict better mental health, however, social comparisons on Facebook were detrimental to mental health (Jang et al, 2016).…”
Section: Mental Healthmentioning
confidence: 99%
“…Thereby, Liu and Yu (2013) argued that although the use of Facebook certainly implies a perception of greater social support, this is weakly linked to well-being, because this relationship is mediated by general social support, received outside SNS. Lima et al (2017) highlighted the positive effects of online friendships compared to face-to-face relationships. Furthermore, Arampatzi et al (2018) established that online social contacts will never replace the role and prominence of real-life social contacts in the human pursuit of happiness.…”
Section: Introductionmentioning
confidence: 99%